2015
DOI: 10.1158/0008-5472.can-14-1931
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Radiosensitization by Monomethyl Auristatin E: Mechanism of Action and Targeted Delivery

Abstract: Intrinsic tumor resistance to radiotherapy limits the efficacy of ionizing radiation (IR). Sensitizing cancer cells specifically to IR would improve tumor control and decrease normal tissue toxicity. The development of tumor targeting technologies allows for developing potent radiosensitizing drugs. We hypothesized that the anti-tubulin agent monomethyl auristatin E (MMAE), a component of a clinically approved antibody-directed conjugate, could function as a potent radiosensitizer and be selectively delivered … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 46 publications
5
54
0
Order By: Relevance
“…Radiation could help to reduce the fibrotic microenvironment by modifying tumor permeability and vasculature, and decreasing interstitial fluid pressure, thus favoring the tumor cell uptake of drugs, such as HER3‐ADC. Interestingly, it has been suggested that radiation induces a “proteolytic switch” by modulating protease activity in the PDAC microenvironment, thus facilitating the localized delivery of therapeutics in tumors. On the other side, HER3‐ADC‐induced radiosensitization will reduce hypoxia‐mediated radioresistance in the PDAC microenvironment.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Radiation could help to reduce the fibrotic microenvironment by modifying tumor permeability and vasculature, and decreasing interstitial fluid pressure, thus favoring the tumor cell uptake of drugs, such as HER3‐ADC. Interestingly, it has been suggested that radiation induces a “proteolytic switch” by modulating protease activity in the PDAC microenvironment, thus facilitating the localized delivery of therapeutics in tumors. On the other side, HER3‐ADC‐induced radiosensitization will reduce hypoxia‐mediated radioresistance in the PDAC microenvironment.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, by indirectly affecting HER2/HER3 heterodimer formation upon binding to HER3, as we previously demonstrated for the naked antibody 9F7–F11, HER3‐ADC could modulate HER2‐mediated activation of ATM/ATR signaling, CHK1 and CHK2 phosphorylation, leading to G2/M arrest . This effect could be additive with the MMAE‐mediated upregulation of DNA damage checkpoint proteins in irradiated cells . Incubation with HER3‐ADC before irradiation synergistically reduced phosphorylation of STAT3 and STAT5 in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, β 3 integrins are overexpressed specially in solid tumors rather than in liver and kidneys from HCT116 human colonic cancer xenografts ( Figure 5B). 29 As a specific recognition site on the ligands for β 3 , cRGD can be modified on liposomes to produce a HCT116-targeted apatinib delivery system.…”
Section: Western Blottingmentioning
confidence: 99%
“…The use of the MMAE‐ACPP conjugate 101 as a radiosensitizer for combination chemo/radiotherapy was investigated by the same group . RGD‐targeted MMAE–ACPP conjugate 101 was shown to sensitize human colorectal and pancreatic cancer cells to radiation, resulting in increased DNA damage upon dual treatment .…”
Section: Targeted Delivery Of Mollusk‐derived Anticancer Agentsmentioning
confidence: 99%